2021
DOI: 10.1097/oi9.0000000000000096
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on orthopaedic residents—an Indian perspective

Abstract: Objectives: The COVID-19 pandemic is a public health emergency causing a deleterious effect on the health system. It affected all the specialties and subspecialties in the medical field causing havoc in the health institutions. This pandemic affected both orthopaedic consultants and the residents who are under training. Our purpose was to study the impact of COVID-19 on orthopaedic residents in their professional life.Method: The study design was a computer-based digital online survey of the orthopaedic reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…4 Literature showed negative impact of COVID-19 pandemic on overall mental health of trainees. [15][16][17][18] Our findings indicated a decline in mental health of orthopedic residents. Many orthopedic trainees spent difficult times isolated, quarantined, or pulled out of orthopedic field as frontliners managing non-orthopedic medical conditions.…”
mentioning
confidence: 56%
“…4 Literature showed negative impact of COVID-19 pandemic on overall mental health of trainees. [15][16][17][18] Our findings indicated a decline in mental health of orthopedic residents. Many orthopedic trainees spent difficult times isolated, quarantined, or pulled out of orthopedic field as frontliners managing non-orthopedic medical conditions.…”
mentioning
confidence: 56%
“…One of those studies investigated the impact of the COVID-19 pandemic on orthopaedic surgery residency training in the United States and reported that the pandemic caused significant changes in the training experience of orthopaedic surgery residents, remarkably reduced clinical working hours and case volume, and led to worsening in such training [ 8 ]. A similar study conducted in India concluded that the COVID-19 pandemic adversely affected the academic training of residents, their surgical exposure and hands-on training [ 9 ]. Although our hospital does not provide resident training due to being a secondary care public hospital, we believe that the pandemic has had negative effects not only on the training of orthopaedics and traumatology residents but also on the surgical practices of orthopaedics and traumatology specialists, since frequent elective surgery cases were halted, especially in public hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…The body of residents was divided into teams, some were given thetask of serving patients with COVID-19, other teams were given orthopedic tasks, and some of the residents werekept in quarantine [ 8 ]. The pandemic has significantly affected residents’ academic teaching, academic examinations, surgical exposure, practical training, and mental stress related to COVID-19 duties [ 9 ].…”
Section: Introductionmentioning
confidence: 99%